2005
DOI: 10.1111/j.1600-0722.2005.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a profilometrical method for monitoring erosive tooth wear

Abstract: The in vivo monitoring of erosive wear is difficult because lesions mostly progress relatively slowly and reliable reference points are difficult to obtain. To date, only a few methods for clinical monitoring of erosive loss have been described, which either require extensive equipment or do not provide sufficient sensitivity. The aim of the present study was to evaluate, using study models (epoxy resin material), a procedure that permits the reliable and accurate monitoring of erosive substance loss within ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 30 publications
0
22
0
2
Order By: Relevance
“…In vitro erosive demineralisation with acids (of clinically relevant amounts and time durations) results in a dissolution of mineral with persisting organic matrix [15]. With the model of cyclic de-and remineralisation used in the present study, loss of mineral in the order of 90 µm occurs [16], thus resulting in a broad zone of demineralised organic matrix on the dentin surfaces. These dentin surfaces appear wet, soft and resilient -a pattern which is not observed clinically.…”
Section: Discussionmentioning
confidence: 91%
“…In vitro erosive demineralisation with acids (of clinically relevant amounts and time durations) results in a dissolution of mineral with persisting organic matrix [15]. With the model of cyclic de-and remineralisation used in the present study, loss of mineral in the order of 90 µm occurs [16], thus resulting in a broad zone of demineralised organic matrix on the dentin surfaces. These dentin surfaces appear wet, soft and resilient -a pattern which is not observed clinically.…”
Section: Discussionmentioning
confidence: 91%
“…For this purpose, high-quality replicas are used and a method for superimposing the surface profiles at different times is required. Ground marks [Lambrechts et al, 1989] or acid-resistant markers bonded to tooth surfaces [Bartlett et al, 1997;Schlueter et al, 2005] have been used to provide fixed reference points, resulting in a detection limit of approximately 15-20 m. Chadwick et al [1997] developed a surface-mapping instrument, which employs a computercontrolled probe to map electroconductive replicas of tooth surfaces. Mitchell et al [2003] estimated that this method had an overall precision of about 15 m and hence a detection limit of about 50 m.…”
Section: Surface Profilometrymentioning
confidence: 99%
“…This fact was also pointed out by Bartlett et al [1997]. Schlueter et al [2005] improved the experimental setting and utilized star-shaped references in order to ensure the identification of the reference points and thereby optimized the precision of the repeated measurements. In the present study, baseline images of the experimental area including the amalgam reference were imaged by the WLI.…”
Section: Discussionmentioning
confidence: 98%
“…Attin et al [2009] reported the detection limit of a mechanical stylus to be 0.105 m, and the precision was 0.031 m which is better than the 0.33 m of SP in the present study. Schlueter et al [2005] performed analyses by mechanical stylus both on epoxy models and enamel surfaces. They reported a detection threshold for etch depth analysis on epoxy models of 15 m, and the measurements on ground enamel surfaces were 0.7 m less precise than the values reported in the present study.…”
Section: Discussionmentioning
confidence: 99%